1992
DOI: 10.1161/01.str.23.1.87
|View full text |Cite
|
Sign up to set email alerts
|

Effect of calcium antagonists on postischemic protein biosynthesis in gerbil brain.

Abstract: Background and Purpose: Prolonged inhibition of protein synthesis precedes delayed neuronal death in the CA1 sector of the hippocampus after transient cerebral ischemia. Organic calcium antagonists have been recommended for alleviation of ischemic neuronal damage. The present study was undertaken to investigate whether these drugs improve the recovery of protein biosynthesis after interruption of cerebral blood flow.Methods: Cerebral protein synthesis was measured biochemically and autoradiographically in gerb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1992
1992
1999
1999

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…This latter finding supports the hypothesis that calcium antagonists have a protective effect on acid-base homeostasis (Bielenberg et al 1990). Administration of nimodipine after experimental ischaemia had no effect on protein biosynthesis in gerbil brain (Xie et al 1992).…”
Section: Metabolic Effectsmentioning
confidence: 82%
“…This latter finding supports the hypothesis that calcium antagonists have a protective effect on acid-base homeostasis (Bielenberg et al 1990). Administration of nimodipine after experimental ischaemia had no effect on protein biosynthesis in gerbil brain (Xie et al 1992).…”
Section: Metabolic Effectsmentioning
confidence: 82%
“…Prolonged inhibition of protein synthesis, if uncompensated by a decrease in breakdown of protein, would clearly lead to massive changes in cell properties and cell death. Protein synthesis is a complex process that is critically dependent on energy charge (936), intracellular K ϩ /Na ϩ (672), and the integrity and phosphorylation level of a large number of proteins and RNA species (1230). It is strongly and permanently inhibited by ischemia in vulnerable cells, and the question is whether or not this is responsible for any forms of ischemic cell death.…”
Section: Global Inhibition Of Protein Synthesismentioning
confidence: 99%
“…There is conflict as to the basis for this inhibition. A priori, phosphorylation of EIF-2a or dephosphorylation of guanine nucleotide exchange factor (GEF) are the most likely inhibitory points (466,1230). One set of studies concluded that there was no increase in EIF-2a phosphorylation but demonstrated a decrease in GEF activity that appeared to be due to dephosphorylation of a site that was normally phosphorylated by a tyrosine kinase.…”
Section: Basis For Prolonged Inhibition Of Protein Synthesismentioning
confidence: 99%
“…The rate of L-[methyl-'H]-methionine incorporation into protein was measured using a modification of the method described by Xie et al 21 Tissue samples were weighed and homogenized with a polytron in 2 mL ice-cold water. After removing an aliquot to determine total tritium levels, 2.5 mL of ice-cold 10% trichloroacetic acid (TCA) was added and incubated on ice for 30 minutes.…”
mentioning
confidence: 99%